2010
DOI: 10.1074/jbc.m109.058313
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharides Up-regulate Kir6.1/SUR2B Channel Expression and Enhance Vascular KATP Channel Activity via NF-κB-dependent Signaling

Abstract: Sepsis is a severe medical condition causing a large number of deaths worldwide. Recent studies indicate that the septic susceptibility is attributable to the vascular ATP-sensitive K ؉ (K ATP ) channel. However, the mechanisms underlying the channel modulation in sepsis are still unclear. Here we show evidence for the modulation of vascular K ATP channel by septic pathogen lipopolysaccharides (LPS). In isolated mesenteric arterial rings, phenylephrine (PE) produced concentration-dependent vasoconstriction tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 36 publications
(47 reference statements)
2
35
0
1
Order By: Relevance
“…Electrophysiology-Patch clamp experiments were performed according to our previous reports (13)(14)(15)(16)(17)(18). Whole-cell currents were recorded in voltage clamp with a holding potential of 0 mV and a hyperpolarizing step to Ϫ80 mV.…”
Section: Methodsmentioning
confidence: 99%
“…Electrophysiology-Patch clamp experiments were performed according to our previous reports (13)(14)(15)(16)(17)(18). Whole-cell currents were recorded in voltage clamp with a holding potential of 0 mV and a hyperpolarizing step to Ϫ80 mV.…”
Section: Methodsmentioning
confidence: 99%
“…Bacterial endotoxins, such as lipopolysaccharide (LPS), have previously been shown to induce excessive activation and up regulation of vascular K ATP channels, to induce hypotension and to substantially reduce vascular sensitivity to vasoconstrictive agents [26,27]. H 2 S has been proposed as a potential endogenous ligand for K ATP channels and induces K ATP channel-mediated vasorelaxation [28] in several vascular tissues, promoting speculation that H 2 S may play a role in endotoxic shock, an important form of acute inflammation, as mentioned.…”
Section: H 2 S and Acute Whole-body Inflammation (Sepsis)mentioning
confidence: 99%
“…In an experimental colitis animal model, the activities and gene expression of K ATP are increased in colonic myocytes [23]. It has been reported that LPS increased the activity and gene expression of K ATP channels in vascular tissue and cells [24,25]. Previously, we found that H 2 O 2 , an inflammatory mediator, suppresses pacemaker activities by the activation of K ATP channels in mouse in- testinal ICCs [26].…”
Section: Discussionmentioning
confidence: 99%